THE ROLE OF STYLISTIC ANALYSIS OF FIGURATIVE LANGUAGE IN SHAPING THE THEME OF RACE IN CHIMAMANDA ADICHIE’S “AMERICANAH” - Dojack, Luciano; Abu-Obeida, Dr. Zahir (IJRDO - Journal of Social Science and Humanities Research, 2023)
The article aimed at stylistic study of figurative language and its role in reflecting the theme of race in Chimamanda Adichie’s Americanah. The article aimed at studying the impressive style of Chimamanda Ngozi Adichie. The researcher used a qualitative approach, besides critical analytical descriptive method. The researcher adopted two theories of Postcolonial Theory and Critical Discourse Analysis (CDA) for the theoretical framework. Some findings of the study are as follows: figurative language plays a great role in reflecting the theme of race in an impressive manner; Chimamanda Adichie uses figurative language in an effective way that reflects race theme vividly. Some recommendations are as follows: introducing teaching of figurative language in all educational stages to produce more future creative African writers; handling race issue in a constructive way that leads to positive outcome when writing literary works that discuss this sensitive theme.